2015
DOI: 10.3144/expresspolymlett.2015.53
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bisphenol-A on the structures and properties of phthalonitrile-based resin containing benzoxazine

Abstract: Abstract. Phthalonitrile and benzoxazine have been considered as high-performance materials in the field of heterocyclic chemistry. The polymerization of phthalonitrile and benzoxazine accelerated by active phenolic hydroxyl has attracted wide interests. In this work, self-promoted polymerization behavior and processability of phthalonitrile containing benzoxazine (BA-ph) with bisphenol-A (BPA) were investigated. Results revealed that BA-ph/BPA exhibited representative doublestage curing behaviors correspondin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 42 publications
3
31
1
Order By: Relevance
“…Meanwhile, the intensity absorption band at 2237 cm −1 assigning to cyano groups became lower with the increase of temperature, suggested the high polymerization degree of cyano groups. However, it is clearly seen that a small amount of cyano group was existed which is agreed with the previous reports . Additionally, triazine rings (1360 cm −1 ) or phthalocyanine rings (1010 cm −1 ) were formed through polymerization of cyano groups .…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Meanwhile, the intensity absorption band at 2237 cm −1 assigning to cyano groups became lower with the increase of temperature, suggested the high polymerization degree of cyano groups. However, it is clearly seen that a small amount of cyano group was existed which is agreed with the previous reports . Additionally, triazine rings (1360 cm −1 ) or phthalocyanine rings (1010 cm −1 ) were formed through polymerization of cyano groups .…”
Section: Resultssupporting
confidence: 91%
“…It can undergo thermal polymerization to obtain a class of high‐performance resins, and the polymerization occurs through the cyano groups by an addition mechanism to afford heterocyclic cross‐linked products, such as triazine and phthalocyanine . It is worth mentioning that there is a small amount of cyano residue after thermal polymerization through our previous research, and it is well known that the cyano group as “strongly polar” can improve the adhesive properties. Therefore, we speculated that introducing phthalonitrile into BMI would be high‐temperature‐resistant adhesives with other excellent properties.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the peaks at 1370 and 1195 cm −1 were corresponded to the stretching vibration of cyclic benzoxazine and the bands at 827 and 872 cm −1 assigned to the trisubstituted benzene ring. The band at 2968 cm −1 assigned to stretching vibration of −CH 3 was used as internal standard . It can be found that the amount of the trisubstituted benzenes decreased and prominent band of tetrasubstituted benzene appears at 878 cm −1 , meanwhile the bands at 1370, 1195, and 955 cm −1 assigned to the characteristic absorption of benzoxazine and disappeared after being cured for 30 min.…”
Section: Resultsmentioning
confidence: 99%
“…Results indicated that the novolac/BAPh blends have a large processing windows (>98°C) and good thermal stability (∼487°C) after being cured at 290°C. The curing behavior of phthalonitrile containing benzoxazine (BA‐ph)/BPA copolymers was thoroughly investigated by Xu et al . Its distinct find was that, with the introduction of BPA, the exotherm bands shift to a lower temperature range (183–210°C), attributing to the fact that the Mannich bridge structure could be formed more easily in the presence of phenolic hydroxyl.…”
Section: Introductionmentioning
confidence: 99%
“…Phthalonitrile‐containing polymers is well known as a class of high‐performance material with high temperature resistance . Monomers and oligomers bearing reactive phthalonitrile units as terminal or pendant functionalities can yield highly cross‐linked thermosets via thermally induced polymerization .…”
Section: Introductionmentioning
confidence: 99%